ChemInform Abstract: Mediator Enhanced Water Oxidation Using Rb4[RuII(bipy)3]5 [RuIII4O4(OH)2 (H2O)4 (γ‐SiW10O36)2] Film Modified Electrodes. Issue 38 (10th September 2014) - Guo, Si‐Xuan; Lee, Chong‐Yong; Zhang, Jie; Bond, Alan M.; Geletii, Yurii V.; Hill, Craig L.
Abstract The H2O insoluble complex of title ([RuIIbipy]5[RuIII4POM]) is prepared by reduction of Rb8K2 [RuIV4O4(OH)2 (H2O)4 (γ‐SiW10O36)2] with NaBH4 followed by precipitation with [Ru(bipy)3]Cl2.